IMPACTS OF CLIMATE DANGER ON COTTON PRODUCTION IN THE SECOND AGRICULTURAL DEVELOPMENT POLE IN NORTH BENIN - ETENE, CYR GERVAIS; BOKO, Patrice Maximilien (My University, 2021)
Climate dereglement and cotton production in Kandi district in Northern Benin” Cotton production is one of theagricultural sub-sectors potentially affected by the variability of climate patterns in West Africa. This study analyzes the incidences of climate variability on cotton cultivation in the district of Kandi. This analysis is based on climate data (rainfalland temperature) for the period 1971-2015 and statistics of area and yield of cotton production on the period 1995-2010. The pluviometric anomalies vary between -2.21 to + 2.64 and the temperatures from - 1.59 to 2.20. The various treatments of quantitative data were reinforced by socio-anthropological qualitative data from fieldwork. The results reveal unimodal rainfall with a rainy season (May to October) and a dry season (November to April). The annual change in rainfall over the period 1971-2015 shows an upward trend marked by 48% of deficit, 3% of average and 49% of surplus years. The problem in the district of Kandi is related to changes in precipitation. In addition, the average temperature has increased by 1.9 ° C. All these parameters affect cotton production and performance. The traditional agricultural calendar is subject to disruption according to climatic variations. In response, farmers are developing several coping strategies to cope with the impacts to which they are subject. These results may be useful in the context of accompanying policies that could help improve the well-being of common farming.
Keywords: Climate Variability; Cotton Production; Adaptation Strategy; Kandi District.